Research note transmission potential of Wuchereria bancrofti by Culex quinquefasciatus in urban areas of Malaysia - Vythilingam, Indra; Huat, T.C.; Ahmad, N.W. (Malaysian Society of Parasitology and Tropical Medicine, 2005)
Laboratory strain of the Malaysian Culex quinquefasciatus was susceptible to Wuchereria bancrofti. Thirty three percent of the Cx. quinquefasciatus that fed on W. bancrofti patient were infective after 12-14 days. There is a possibility for W. bancrofti to occur in the urban areas of the Malaysia in the near future.